Manajemen Kurikulum Pendidikan Dasar - Indah S, Hofifah; Nurhidayah, Nurhidayah In; Farida, Siti Nur (UAS PRESS, 2024)
Basic education is the initial level of the national education system which aims to develop attitudes, abilities, and provide basic knowledge and skills needed to live in society and prepare students to continue to secondary level education. Basic education covers nine years, namely six years in elementary school and three years in junior high school. This article will discuss various aspects related to curriculum development policy in Indonesia, including the basics and principles of curriculum development, curriculum structure, and the curriculum design process.